Violence against children and adolescents in times of pandemic: integrative literature review (Research, Society and Development, 2022)
Introduction: COVID-19 emerged in late 2019 in Wuhan, China, and was declared by the World Health Organization (WHO) as the sixth public health emergency. In this sense, children and adolescents found themselves in a condition of greater susceptibility to abuse by those responsible. Objective: To identify through literature data which factors are associated with the increase in violence against children and adolescents during the COVID-19 pandemic. Method: This is an integrative literature review, in which the construction of the study was based on the question “What were the reasons that evidenced the increase in child/adolescent violence in social isolation in times of COVID-19?”. The bibliographic survey was carried out between November and December 2021, using PubMed, Cochrane, Scielo and Lilacs databases. The selection of studies was carried out in two stages. Results: Searches in the databases resulted in 25 references, 12 articles were excluded, nine were reviews, and three were due to the unavailability of the full text. The remaining 13 articles were read in their entirety independently, making up the final sample of this review. It was possible to identify that the growth of violence against children and adolescents in the pandemic happened due to the greater exposure of the child to situations of vulnerability. Conclusion: The increase in violence against children and adolescents has numerous justifications, but it is possible to affirm that social isolation provided the ideal set for the aggressor to commit his crimes against children and adolescents, reducing the chances of defending the victims.